Opening the Black Box of the Matching Function: The Power of Words - Ioana E. Marinescu; Ronald P. Wolthoff (Institute for the Study of Labor (IZA), 2015)
How do employers attract the right workers? How important are posted wages vs. other job characteristics? Using data from the leading job board CareerBuilder.com, we show that most vacancies do not post wages, and, for those that do, job titles explain more than 90% of the wage variance. Job titles also explain more than 80% of the across-vacancies variance in the education and experience of applicants. Finally, failing to control for job titles leads to a spurious negative elasticity of labor supply. Thus, our results uncover the previously undocumented power of words in the job matching process.
Keywords: J31; J63; J64; 330; online job search; wages; vacancies; wage variance; occupations; skills